2023
DOI: 10.3390/ani13040549
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Phytase and Non-Starch Polysaccharide-Hydrolyzing Enzymes on Trace Element Deposition, Intestinal Morphology, and Cecal Microbiota of Growing–Finishing Pigs

Abstract: This study investigated the effects of supplementing phytase and non-starch polysaccharide-degrading enzymes (NSPases) to corn–soybean meal-based diet on the growth performance, trace element deposition, and intestinal health of growing–finishing pigs. Fifty pigs were randomly assigned into the control (basal diet), phytase (basal diet + 100 g/t of phytase), β-mannanase (basal diet + 40 g/t of β-mannanase), β-glucanase (basal diet + 100 g/t of β-glucanase), and xylanase (basal diet + 100 g/t of xylanase) group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…These phyla include a diverse range of species, which can have harmful effects in animals [122]. Furthermore, Moita and Kim [123] found a reduced abundance of the Prevotellaceae family in the jejunum of nursery piglets fed 2000 FTU/kg, which aligns with the findings of Liu et al [25]. The Prevotellaceae family is known for its diversity, with some members playing a crucial role in the fermentation of dietary fiber within the intestine [124].…”
Section: Phytasesupporting
confidence: 74%
See 3 more Smart Citations
“…These phyla include a diverse range of species, which can have harmful effects in animals [122]. Furthermore, Moita and Kim [123] found a reduced abundance of the Prevotellaceae family in the jejunum of nursery piglets fed 2000 FTU/kg, which aligns with the findings of Liu et al [25]. The Prevotellaceae family is known for its diversity, with some members playing a crucial role in the fermentation of dietary fiber within the intestine [124].…”
Section: Phytasesupporting
confidence: 74%
“…Considering all the extra-phosphoric effects resulting from phytase supplementation in non-ruminant animal diets, such as the beneficial modulation of the microbiota, reduced activation of the immune system, and improved antioxidant status, it is plausible that there are enhancements in intestinal morphology and barrier function. This has been demonstrated in studies conducted with broiler chickens [24,115,116,132], and pigs [25,114,131], which suggests that improvements in growth performance cannot only be attributed to increased nutrient availability, but also to overall improved intestinal health.…”
Section: Phytasementioning
confidence: 89%
See 2 more Smart Citations
“…According to Adeshina, Akpoilih, Udom, et al (2023), increased intestinal villi width/height and absorption area were caused by the phytase enzyme (1000 FTU/kg) linked to the control group. Feng et al (2016) and Liu et al (2023) found comparable findings. Phytic acid is broken down by phytase to produce inorganic phosphorus and inositol through a process called dephosphorylation, allowing the minerals to be released and then absorbed by the intestine, which can impact its absorptive capacity (Kumar et al, 2012).…”
Section: Discussionmentioning
confidence: 59%